Understanding the Charge Transport Mechanism in MoS2 Transistors with Graphene Electrodes - Jang, Jisu; Hwang, Do Kyung (한국물리학회, 2020)
Two-dimensional transition-metal dichalcogenides (TMDs) have emerged as promising candidates for next-generation electronics owing to their excellent semiconducting properties. However, metal-TMDs junctions are of particular interest as they have become a major limiting factors to further improvements in TMD-based device performance. Here, we investigate the charge transport of MoS2 transistors contacted with Ti/Au and graphene electrodes. Compared to a conventional Ti/Au contact, the MoS2 devices with graphene electrodes exhibit improved electrical properties (field-effect mobility, subthreshold swing, and low off-state current). Such a device improvement could be attributed to efficient electron injection arising from the tunable graphene Fermi level as well as the high hole barrier height, which significantly reduces the off-state current caused by hole transport. Furthermore, a simple Schottky barrier model has been employed to explain the observed transfer characteristic of MoS2 transistors with two different contacts. Our finding provides significant insights into the understanding of charge transport in TMD-based transistors for future 2D electronics.